Enabling smarter routing in WSNs with mobile sinks - Tufail, Ali (International Journal of Engineering and Technology, 2018)
Wireless sensor networks (WSNs) have been increasingly deployed for ambient data reporting for varied settings. Source to the sink communication is typically multi-hop and intermediate nodes relay packets from the source to the destination. Fast energy drainage from the nodes around the sink can affect the overall network lifetime. Mobile sinks are typically utilized to enhance the lifetime of the WSN. However, mobile sinks can bring more challenges to already constrained WSN. When the sink relocates itself location updates and the route request messages can trigger an excessive amount of traffic within the network. This paper proposes a smart routing protocol that can support sink mobility in WSNs at the same time avoiding the excessive route or location update messages. In most of the cases routes are only updated for the first hop neighboring nodes of the sink. The proposed protocol does not require sink to subscribe to any data in advance. Moreover, sink has the freedom to take any arbitrary path. The overhearing characteristic of the wireless transmission has been exploited in order to reduce the routing overhead even further.